Ikrar Cash Waqf for Economic Equality According to Law Number 4 Year 2023 And Islamic Economic Law - Imaniyati, Neni Sri; Firmansyah, Arif; Alamsyah, Indra Fajar; Kamilah, Anita (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Cash Waqf in Islamic Banks for economic equality has become an essential topic in the legal framework regulated by Law Number 4 Year 2023 concerning the Development and Strengthening of the Financial Sector and Islamic Economic Law. Cash waqf in Islamic Banks provides a legal basis for raising funds needed to support economic equality, which aims for sustainable economic development. The purpose of this study is to explain Cash Waqf in Islamic Banks for economic equality, first, according to Law Number 4 Year 2023 concerning the Development and Strengthening of the Financial Sector and, second, according to Islamic Economic Law. The research method used normative juridical with a statute and conceptual approach, while the research specifications used descriptive analytical. The results of the study indicated that Law Number 4 Year 2023 provides a legal framework to support cash waqf in Islamic Banks by providing opportunities for them to become waqf nazirs. Then, this will support national economic equality in accordance with the objectives of waqf according to Islamic economic law. However, harmonization of regulations related to banks as cash waqf nazirs is needed.